The Sources of Competitive Advantage in Modern Business Theories - Časas, Ramūnas (Ekonomika, 2000)
In this article, which is a condensed theoretical part of the doctoral project. the problems of competitive advantage formation are researched. The author argues that one can identify three theoretical positions, explaining how a company generates competitive advantage: 1) through adaptation of the organization to the environment, 2) through endogenous activities or unique internal resources, 3) by establishing linkages to and interaction with other firms and institutions. On the basis of the theoretical positions, three concepts of competitive strategy are developed. At the end of the article. the results of analysis are concluded, describing the conditions of environment and characteristics of the company, necessary to implement one of the above-mentioned concepts of competitive strategy.